2015
DOI: 10.3390/f6072345
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Conservation, Ecotourism, and Sustainable Management: The Case of Penang National Park

Abstract: Penang National Park (PNP), as Malaysia's smallest national park, is one of the few naturally forested areas left on Penang Island, in Peninsular Malaysia. The main objective was to analyse users' preferences and willingness to pay to enhance improved management of PNP for the dual aim of conservation and recreation. Structural equation modelling (SEM) was used to analyse the formation of attitudes towards different aspects of PNP. Results showed that implementing enforcements with rules and regulations and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 40 publications
3
34
0
1
Order By: Relevance
“…This is in line with other studies which indicated that tourists expressed a high interest in more accessible and improved information [8,10,39]. In the studied area, the park authorities are constantly improving the manner in which information is provided to tourists through several funding programs, as they are aware that the quality of a recreational trip can be influenced by the information available.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This is in line with other studies which indicated that tourists expressed a high interest in more accessible and improved information [8,10,39]. In the studied area, the park authorities are constantly improving the manner in which information is provided to tourists through several funding programs, as they are aware that the quality of a recreational trip can be influenced by the information available.…”
Section: Discussionsupporting
confidence: 71%
“…Offering tourism opportunities while minimizing environmental impacts remains an ongoing task for park authorities that should be constantly based on a systematic evaluation of tourists' preferences and behavior [7,8]. Preferences refer to the tradeoffs between social, economic, and ecological values of goods and services provided by the protected areas [9].…”
Section: Introductionmentioning
confidence: 99%
“…Other issues include illegal hunting, poaching of terrestrial animals, and extraction of agarwood. These circumstances in a national park would result in visitor dissatisfaction (Kaffashi et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A choice experiment (an elicitation technique for choice modelling) has the capacity to estimate values for alternative multi-attribute resource-use options. It estimates trade-offs among different attributes of the park, including price, besides the marginal changes in each individual attribute (Kaffashi et al 2015). Information gathered will help the management of ERNP and JNPC managers gauge the relative value of each of the different attributes being evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Ketersediaan pusat informasi dan pemandu wisata menjadi hal yang penting bagi pengunjung yang baru pertama kali berkunjung ke lokasi wisata (Lindberg dan Veisten, 2012). Variabel biaya yang ditambahkan kedalam harga tiket masuk tidak menjadi permasalahan bagi sebagian besar pengunjung karena informasi yang didapat menjadi kepuasan pengunjung (Kaffashi et al, 2015).…”
unclassified